B Corp certification in Europe: an analysis of impact and growth opportunities - Tröger, Katrin (2022)
Over the last decade, companies have faced increasing pressure to adopt a 'triple bottom line' mentality, leading to the expansion of hybrid enterprises. The challenge to demonstrate the authenticity of ethical practices resulted in the growing popularity of the B Corp certificate. It holistically assesses social and environmental contributions, creating a movement of businesses ‘as a force for good’. As the US label is less widespread in Europe, this study examines the impact of certification on European B Corps, highlighting factors that might enhance or diminish certification benefits. Moreover, it provides an analysis of the certificate’s growth prospects and challenges.